The algorithm's gaze: Gender, age, and the structuring of TikTok content consumption patterns in urban Indonesia (A case study in Surabaya) - Suharnanik, Suharnanik; Emanuel, Endrayana Putut Laksminto; Ashfaq, Asia (INTERNATIONAL JOURNAL OF CHILD AND GENDER STUDIES, 2025)
TikTok was one of the fastest-growing social media platforms in Indonesia, particularly among Gen Z and millennials. This article aimed to analyze the role of the TikTok algorithm in shaping content consumption patterns based on gender and age. The study employed a qualitative approach using two main techniques. First, content analysis was conducted on 200 popular videos appearing on the For You Page to identify thematic tendencies. Second, in-depth interviews were carried out with 30 active users in Surabaya (15 women and 15 men), selected purposively based on the intensity of their usage and the diversity of their backgrounds. These findings were complemented with data from two audiences’ insight platforms revealing fluctuating gender distribution among TikTok users in Indonesia. At certain periods, women dominated the user base, while at other times, men accounted for a higher percentage. This dynamic indicated that the TikTok algorithm was responsive not only to individual preferences but also to demographic shifts. The results showed that women were more likely to consume lifestyle, beauty, and aesthetic-related content, whereas men more frequently engaged with humor, sports, and technology. The novelty of this study lay in the finding that Gen Z demonstrated flexibility in crossing gender stereotypes; for instance, women actively engaged with technology content, while men were interested in beauty-related content. Thus, the TikTok algorithm functioned both to reinforce gender- and age-based preferences and to provide space for identity negotiation within the digital cultural sphere. This study contributed to gender, technology, and social media studies in Indonesia.